Investigation of wave-driven hydroelastic interactions using numerical and physical modelling approaches. (December 2022) - Brown, S.A.; Xie, N.; Hann, M.R.; Greaves, D.M.
Abstract: Wave-driven hydroelasticity is of great importance to a wide range of applications within offshore and coastal engineering. Harnessing the benefits of hydroelasticity or minimising its impacts, depending on the application, has recently led to substantial investment in research effort in this field. However, the complex and strongly-coupled nature of the problem generally make the impacts very case specific, highlighting the importance of accurate numerical tools for assessing the impact on a case-by-case basis. Therefore, this study aims to provide novel experimental data to assist with the development of a coupled numerical methodology for simulating fully nonlinear hydroelastic interactions with highly-flexible floating structures. Novel physical data from a laboratory campaign conducted at the University of Plymouth is presented, and used as a reference for assessing the capabilities of an existing coupled numerical approach. The numerical model is a partitioned approach based within the open-source computational fluid dynamics software OpenFOAM and consisting of a two-phase fluid solver; a linear solid model for small deformations solved via the block-coupled method; and strongly-coupled through the Dirichlet–Neumann method with dynamic Aitken under-relaxation. The numerical model is shown to capture well the wave-induced deformation, and the qualitative differences between structures of varying dimensions. However, the high computational cost limits the scope of this work to 2-D, and future work should focus on optimising the approach to allow for application in 3-D problems.